2019
DOI: 10.1016/j.jcmg.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Afterload Hypersensitivity in Patients With Left Bundle Branch Block

Abstract: Moderate elevation of arterial pressure caused marked reductions in LVEF and GLS in patients with LBBB. This reflects a cardiodepressive effect of elevated afterload in the dyssynchronous ventricle and was attributed to loss of septal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 29 publications
3
17
0
2
Order By: Relevance
“…Therefore, not only septal deformation pattern, but also septal pump function was markedly improved when the LV lateral wall was dysfunctional. In a recent study of patients with LBBB we also demonstrated a strong afterload dependency of septal motion (28). In that study we showed aggravation of septal dysfunction with enhanced septal rebound stretch during acute elevation of aortic pressure (28).…”
Section: Modifiers Of Abnormal Septal Motion In Lbbbsupporting
confidence: 58%
“…Therefore, not only septal deformation pattern, but also septal pump function was markedly improved when the LV lateral wall was dysfunctional. In a recent study of patients with LBBB we also demonstrated a strong afterload dependency of septal motion (28). In that study we showed aggravation of septal dysfunction with enhanced septal rebound stretch during acute elevation of aortic pressure (28).…”
Section: Modifiers Of Abnormal Septal Motion In Lbbbsupporting
confidence: 58%
“…Esse modelo associado ao MultiPatch Module, apresentado por Walmsley et al, 11 pode retornar curvas de strain correspondentes às simulações e os tempos de eventos mecânicos, sem sinais de ECG, como mostrado na Figura 6. Dessa forma, o software desenvolvido pode trabalhar com modelos cardíacos virtuais elaborados seguindo o trabalho de Walmsley et al [11][12][13][14] Possibilidade de aplicação de técnicas de aprendizado de máquina (Machine Learning) Machine learning consiste em uma área do campo da inteligência artificial capaz de processar problemas complexos de interação entre variáveis e fazer predições acuradas. Tem sido amplamente utilizada em diferentes áreas da cardiologia.…”
Section: Resultsunclassified
“…A interface do D-Station com o modelo Circadapt associado ao MultiPatch Module permite formulação de hipóteses e comparação com sinais de pacientes reais como já realizado previamente. [12][13][14] Isso gera recursos de ensino da fisiopatologia da deformação cardíaca, além de potencialmente reduzir o tempo da escolha das variáveis de interesse e poupar recursos com elaboração de modelos animais em alguns cenários de pesquisa.…”
Section: Potenciais Aplicações Do Software D-stationunclassified
“…Aalen et al have shown that the dyssynchronous ventricle is particularly sensitive to increase in LV afterload. This is particularly evident in the septum with respect to the lateral wall [21], and might explain the relationship between septal work efficiency and exercise performance in patients with LV-DYS. In a small cohort of patients undergoing CRT, Zweerink et al have shown that the contribution of the septum to LV work varies widely in CRT candidates and that the lower is the septal contribution to myocardial work at baseline, the higher is the acute pump function improvement that can be achieved with CRT [22].…”
Section: Several Methods Mostly Based On the Analysis Of Timing Of Lomentioning
confidence: 91%